Morphological and Genetic Variation in Monocultures, Forestry Systems and Wild Populations of Agave maximiliana of Western Mexico: Implications for Its Conservation - Cabrera-Toledo, Dánae; Vargas-Ponce, Ofelia; Ascencio-Ramírez, Sabina; Valadez-Sandoval, Luis Mario; Pérez-Alquicira, Jessica; Morales-Saavedra, Judith; Huerta-Galván, Oassis F. (Frontiers in Plant Science, 2020)
Forestry systems in Mexico are examples of traditional management of land and biodiversity that integrates the use, conservation and restoration of forest elements. Current in situ management practices of Agave maximiliana in western Mexico include the tolerance of many forest elements, reintroduction of young Agave plants and germination of seeds. More intense forms of management include monocultures, which are agroindustrialized systems developed in more recent times and characterized by the establishment of high densities of A. maximiliana plants in deforested areas and abandoned agricultural lands. We compared monocultures, forestry systems and wild populations (i.e., non/slightly-exploited forests) in order to evaluate whether these practices have had an effect on intraspecific morphological and genetic variation and divergence. We also tested whether divergence has a positive relationship with environmental and geographic distance. We analyzed 16 phenotypic traits in 17 populations of A. maximiliana, and 14 populations were further examined by amplifying 9 SSR loci. We employed multivariate methods and analyses of variance in phenotypic and genetic traits to test whether clusters and the percentage of variation contained in the managed and wild categories can be identified. Tests of isolation by environment (IBE) and distance (IBD) were performed to detect the magnitude of divergence explained by climatic and geographic variables. We found that forestry systems are effective as reservoirs of morphological and genetic diversity, since they maintain levels similar to those of wild populations. Moreover, the monocultures showed similar levels, reflecting their recent emergence. While the species showed high morphological diversity (IMD = 0.638, SE ± 0.07), it had low to intermediate genetic diversity (A = 2.37, HE = 0.418). Similar morphological and genetic divergences were found among populations, but these were not correlated with each other in population pairs. Non-significant morphological differentiation was found among categories. Only IBE was significant in the genetic structure (β = 0.32, p = 0.007), while neither IBE nor IBD was detected in the morphological differentiation. We discuss the implications of these results in the context of the weaknesses and strengths of A. maximiliana in the face of the socio-ecological changes predicted for the study area in the short term.